2018
DOI: 10.1038/s41431-018-0288-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional reassessment of PAX6 single nucleotide variants by in vitro splicing assay

Abstract: Nucleotide variants that disrupt normal splicing might be the cause of a large number of diseases. Nevertheless, because of the complexity of splicing regulation, it is not always possible to accurately predict the effect of nucleotide sequence changes on splicing events and mRNA structure. Thereby, a number of newly identified nucleotide variants are falsely classified as VUS (a variant of uncertain significance). In the present study we used the minigene assay to analyze the functional consequences of six in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
(16 reference statements)
1
22
0
Order By: Relevance
“…2b). 4 The result confirmed that the EDA c.801A>G variant leads to exon 7 skipping. The absence of the exon 7 in the structure of mature EDA mRNA leads to a frame shift resulting in a truncated non-functional EDA protein p.(D265Gfs7*), lacking part of the conserved motifs in the TNF-related domain and the whole cysteine-rich C-terminal domain.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…2b). 4 The result confirmed that the EDA c.801A>G variant leads to exon 7 skipping. The absence of the exon 7 in the structure of mature EDA mRNA leads to a frame shift resulting in a truncated non-functional EDA protein p.(D265Gfs7*), lacking part of the conserved motifs in the TNF-related domain and the whole cysteine-rich C-terminal domain.…”
supporting
confidence: 53%
“…Only one non-compliant patient required a section due to LS-related scarring. 4 One patient developed LS in a perineal scar. Two women with newly diagnosed LS and who delivered by normal spontaneous vaginal delivery without problems have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The deletions or point mutations in non-translated 5' and 3'UTR of PAX6 have also been reported [75,97,98]. Minigene assays or in silico analysis revealed that most of these variants are likely to affect the normal splicing patterns, which results in the formation of PTCs and the consequent PAX6 haploinsufficiency [99].…”
Section: Non-coding Variantsmentioning
confidence: 99%
“…To determine functional significance of the c.2094G>T (p.(Lys698Asn)) variant, we applied the minigene assay as previously described [9]. Exon-of-interest with about 300 bp of flanking intronic sequences was cloned into pSpl3-Flu2 vector.…”
Section: Methodsmentioning
confidence: 99%